Flood Alarm Prototype: A STEAM Project to Study Physics and Building Students’ Awareness of Natural Disasters - Inanda Aulia Rizqillah; Eko Hariyono; Daliana Fehabutar (Indonesia Approach Education, 2022)
Indonesia is a country with a significant portion of its territory consisting of water bodies, which makes it prone to flooding. Therefore, the development of an early warning system in the form of a flood alarm prototype is crucial. This research is designed using the Design Thinking models method. Based on the created prototype, STEAM-based learning can be implemented to enable students to learn physics through scientific steps. It also fosters critical thinking, creativity, collaboration, and communication skills in accordance with the 21st-century concept, while increasing students' awareness of natural disasters in their surroundings.